Prevalence of Polycystic Ovarian Syndrome in Girls with a History of Idiopathic Central Precocious Puberty - Arcari, Andrea Josefina (2023)
Introduction: The prevalence of polycystic ovarian syndrome (PCOS) in adolescent girls is between 1 and 4.3%. It remains controversial whether women with a history of idiopathic central precocious puberty (ICPP) are at increased risk for PCOS. Our objective was to assess the prevalence of PCOS in adolescents with a history of ICPP compared with healthy adolescents and the prevalence of PCOS among ICPP girls who have received or not gonadotropin-releasing hormone analogue (GnRHa) treatment.Methods: We assessed post-menarcheal girls with a history of ICPP. Girls were evaluated at gynecological age ≥2.5 years. Data collected were age at menarche, menstrual cycle characteristics, BMI, clinical hyperandrogenism (HA), total and free testosterone levels. PCOS diagnosis was defined by criteria for adolescents. Subjects were also analyzed regarding whether or not they had received GnRHa treatment.Results: Ninety-four subjects were assessed, and 63 had been treated with GnRHa. Menstrual disorders were found in 29%, clinical HA in 36%, and biochemical HA in 23%. Twelve percent met the diagnostic criteria for PCOS. There was no difference in BMI or in the incidence of menstrual dysfunction or hyperandrogenemia between treated and untreated patients. A higher proportion of clinical HA was found in untreated patients when compared to treated girls. The relative risk (RR) of developing PCOS in ICPP girls was 2.5 compared to a population of healthy adolescents. This RR was not higher in patients who received treatment with GnRHa than in those who did not.Conclusion: Adolescent girls with a history of ICPP have an increased risk of PCOS. This risk seems not to be related to GnRHa treatment.